Self –Delusion in Doris Lessing’s The Grass is Singing (1950) - Khedir, Luqman Omer; Al-Banna, Juan Abdullah Ibrahim (Al-Adab Journal, 2023)
This study presents Doris Lessing as one of the most accomplished and significant British writers of the post-World War II generation. Her work looks into The Grass is Singing (1950) from a psychological, socio-cultural and economic point of view. It attempts to analyze the bleak and the tragic causes and effects of self-delusion in the lives of female and male characters alike in a racist society grappling with a number of deep-rooted social and political misconceptions and misjudgments. Moreover, it showcases a recycled series of psychological problems the main female protagonist faces due to her delusional beliefs which end only with her tragic death. It also sheds light on the importance of knowing oneself in a baffling and fragmented world enmeshed with people caught tight in the grip of self-made delusional conceptions in an attempt to cope with the challenges set by modern life. This fact can be discerned through the analysis of Lessing’s representative novel: The Grass is Singing (1950) from Autobiographical, psychoanalytical and existentialist perspectives to make readers familiar with the destructive power of delusion and self-delusion in life. Lessing tackles issues that are at the essential concern to whole humanity around the world; therefore, this study can be taken as an attempt and an entry point of highlighting some aspects of the creative and innovative intellectual accomplishments of any truly concerned and committed writer with mankind problems in the world regardless to gender, race and educational and cultural background. The study is in two sections. Section one is concerned with the analysis of The Grass is Singing (its abbreviated form is TGS), and Lessing’s narrative creativity through reader’s concentration on causes rather than results. The second section presents racial discrimination and self-delusion in the text, taking childhood trauma into consideration and the issues of Marriage and Self- Delusion followed by conclusions and Bibliography.